BREWING INTERDISCIPLINARY COLLABORATION IN HIGHER EDUCATION:THE CENTRO DE ENSEÑANZA TÉCNICA Y SUPERIOR (CETYS)BrewEd INITIATIVE AS A MODEL FOR COMMUNITY-DRIVEN LEARNING - Núñez Tapia, Francisco Alberto; Vargas Larraguível, Paulina (My University, 2025)
The Centro de Enseñanza TécnicaySuperior (CETYS)BrewEdInitiative demonstrates the transformative power of interdisciplinary collaboration by merging entrepreneurship education withthe Mexicaliregion’scraft brewing industry. This innovative model transforms local businesses into experiential learning environments, integrating academic theory with hands-on practice. Through co-curricular workshops, industry partnerships, and cultural programs, students gain direct exposure to entrepreneurial challenges while reinforcing community ties and fostering sustainable business practices. Early findings underscore BrewEd’s effectiveness in equipping students with applied business skills, fostering awareness of community-driven economic development, and providing a scalable framework for interdisciplinary education. Byblending experiential learning with meaningful industry engagement, BrewEd offers a replicable model for universities aiming to connect education, industry, and cultural heritage—contributing to global conversations on entrepreneurship education, sustainability, and community-driven learning.Keywords:Interdisciplinary Collaboration, Entrepreneurship Education, Experiential Learning, Community Engagement, Sustainable DevelopmentCopyright: ©2025 Núñez-Tapia& Vargas-Larraguível. This is an open access article distributed under the terms of the Creative Commons Noncommercial Attribution license (CC BY -NC 4.0), which allows for unrestricted noncommercial use, distribution, and adaptation, provided that the original author and source are credited.
Interdisciplinary Journal of Partnership Studies
Keywords: Interdisciplinary Collaboration; Interdisciplinary Collaboration; Experiential Learning; Community Engagemen; Sustainable Development; Campus Mexicali